Pelanggaran Imunitas Diplomatik oleh Petugas Imigrasi Indonesia Kajian Yuridis terhadap Konvensi Wina 1961 - Anesva Sari Della; Zahra Utami Aprilia; Firdhan Azhim Akbar; Ema Septaria; M. Ilham Adepio (Journal of Innovative and Creativity, 2025)
Diplomatic Immunity is one of the important things in international relations, which is regulated by the 1961 Vienna Convention to protect diplomats in carrying out their duties. However, the application of this immunity often poses challenges, especially when there is tension between international law and domestic law. Such as in the incident involving Nigerian diplomats who were attacked by Indonesian immigration officers in 2021. This incident raises the question of how the Principle of Diplomatic Immunity Relates to Indonesian Immigration Law and How the Implementation of Indonesian Immigration Law Policy is in the Case of Nigerian Diplomats. This study uses a normative approach with the Statute Approach method, namely the approach to statutory regulations consisting of legal materials and is of a library research nature. The results of this study indicate that, although Indonesia has a strict immigration policy, the protection of diplomatic rights based on the 1961 Vienna Convention has not been fully implemented. Weaknesses in the understanding of officers require increased training on diplomatic immunity, integrated supervision, and alignment of immigration regulations to prevent diplomatic conflicts and maintain the stability of international relations. This study suggests that Indonesia can strengthen immigration officer training on diplomatic immunity, as well as align immigration regulations with the principle of diplomat protection to prevent escalation of diplomatic conflicts and maintain its global reputation.